An approach to long-term sedative-hypnotic use - Shahid A (Dove Medical Press, 2012)
Azmeh Shahid, Sharon A Chung, Ron Phillipson, Colin M ShapiroDepartment of Psychiatry, University of Toronto and Toronto Western Hospital, University Health Network, Toronto, CanadaAbstract: Insomnia is a common, often chronic medical disorder with significant medical and socioeconomic repercussions. However, unlike other medical conditions, there is intense debate as to whether the long-term treatment of insomnia is clinically appropriate. The perceived deleterious side effect of sedative-hypnotic medications may result in patients remaining untreated or undertreated. This review proposes that a more subtle approach needs to be taken in the management of patients with chronic insomnia and that long-term use of the newer sedative-hypnotics may be a feasible and effective treatment option when used in conjunction with thorough medical assessment and regular patient follow-up. This review discusses these issues and discusses the pros and cons of long-term sedative-hypnotic use.Keywords: insomnia, long-term use, hypnotics